Complete spontaneous necrosis of hepatocellular carcinoma confirmed on resection: A case report. (2016) - Saito, Ryusuke; Amano, Hironobu; Abe, Tomoyuki; Fujikuni, Nobuaki; Nakahara, Masahiro; Yonehara, Shuji; Teramen, Kazushi; Noriyuki, Toshio
Highlights: Spontaneous necrosis of hepatocellular carcinoma without any pretreatment or angiography is extremely rare. Spontaneous necrosis of HCC was highly suspected given the history of alcoholic hepatitis, based on the elevation of AFP and the CT findings. The mechanisms of spontaneous regression are still unclear. Recurrence after regression or viable malignant cells in resected specimen are reported. The ideal management strategy for this disease is surgical intervention if the liver function is acceptable. Abstract: Introduction: Complete spontaneous necrosis of hepatocellular carcinoma (HCC) without any pretreatment or angiography is rare. We present a rare case of spontaneous complete necrosis of HCC, as confirmed after hepatectomy. Presentation of case: The patient, a 74-year-old man with a history of alcoholic hepatitis, was referred to our hospital for confirmation of suspected HCC. In March 2015, abdominal ultrasonography detected a low echoic mass in segment 8 (S8) of the liver. Contrast-enhanced computed tomography (CT) imaging revealed interval growth of this tumor and showed that the tumor was well enhanced in the arterial phase and washed out in the portal and delayed phases. The serum alpha-fetoprotein level was elevated at 30.8 ng/mL and the percentage of the L3 isoform was 25.5%. Two months later, CT imaging showed that the tumor was of low density and had decreased in size; no contrast enhancement of the tumor was seen. Spontaneous necrosis of the HCC was considered; however, as we could not exclude viable malignant cells in the tumor, we performed S8 segmentectomy of the liver. The resected tumor specimen had a thick fibrous capsule. Histopathological findings showed only granulation and necrotic tissue accompanied by bleeding and hemosiderosis. No viable tumor cells were observed. The serum alpha-fetoprotein level returned to the normal range one month after surgery. Discussion: If spontaneous regression has occurred, there is a possibility of HCC recurrence and of remnant viable tumor cells. Conclusion: We present a rare case of complete spontaneous necrosis of HCC and strongly recommended surgical intervention.